Plate Girder Design Using LRFD - Zahn, Cynthia J. (Engineering Journal, 1987)
What differentiates a beam from a plate girder? This may seem to be a trivial question. However, it is a necessary and important part of plate girder design when applying the Load and Resistance Factor Design (LRFD) Specification. Making this distinction and the compactness classification early in plate girder design is important when using the LRFD Specification. The significance of these items can be seen in the LRFD Manual flowcharts for the determination of flexural and shear design strength. With these flowcharts, this discussion will focus on the design of plate girders according to LRFD rules. An explanation of plate girder design in the LRFD Specification will include: flexural design strength, shear design strength, flexure-shear interaction, bearing strength under concentrated loads and stiffener design. Application of the LRFD method will show there is actually little difference between it and Allowable Stress Design (ASD) of plate girders.